Correlation between Lower Esophageal Sphincter Metrics on High-Resolution Manometry and the Clinical Presentation of Patients with Newly Diagnosed Achalasia - Daniel L. Cohen; Eyal Avivi; Anton Bermont; Fahmi Shibli; Narges Azzam; Basem Hijazi; Fadi Abu Baker; Vered Richter; Haim Shirin; Amir Mari (Diagnostics, 2023)
Background: Achalasia is characterized by aperistalsis with poor relaxation of the lower esophageal sphincter (LES). We aimed to systematically assess whether LES metrics on high-resolution manometry (HRM) correlate with the symptomatic or endoscopic presentation of patients with achalasia. Methods: A retrospective study was performed at two tertiary medical centers. All cases of newly diagnosed, untreated achalasia were reviewed for demographics, symptoms, and endoscopic findings. These were correlated with HRM metrics, including LES basal pressure (LESP), integrated relaxation pressure (IRP), percent LES relaxation, and esophagogastric junction (EGJ) morphology. Results: 108 achalasia patients were included; 56 (51.9%) were men, with a mean overall age of 55.6 ± 17.9 years old. Achalasia subtypes included 23.1% with Type I, 65.7% Type II, and 11.1% Type III. Mean LESP was 40.9 ± 13.7 mmHg, IRP 26.8 ± 11.5 mmHg, with 36% ± 20% LES relaxation. On univariate analyses, a higher IRP was associated with age < 50 (p = 0.028), female sex (p = 0.030), Arab ethnicity (p < 0.001), weight loss (p = 0.016), a tortuous esophagus (p = 0.036), and resistance at the EGJ (p = 0.033). However, on multivariate regression analyses, only ethnicity remained significantly associated with IRP. No unique variables were associated with either LESP or percent LES relaxation. Achalasia subtype and Eckardt score were not associated with any LES metrics. Non-Type 1 EGJ morphology was associated with a lower LESP. Conclusions: LES metrics on HRM do not appear to correlate with the clinical or endoscopic presentation of patients with untreated achalasia.